Management of Learning Facilities in Public Middle Schools - Seno Sudrajat; Tina Rahmawati (Universitas Pendidikan Ganesha, 2025)
Curriculum changes in schools make school facilities and infrastructure change and differ, from books, tools, and activities. The research in this journal aims to manage learning facilities and infrastructure, and solve problems in managing learning facilities and infrastructure in SMPN. The subjects involved in this study were the Principal, School Treasurer, and Sarpras management staff as the primary data sources. The study used qualitative methods. Data collection techniques: observation, interviews, and documentation. The data analysis used is Miles Huberman, namely, data condensation, presentation, and conclusion. The validity of this research data consists of credibility, transferability, confirmability, and dependability. The use of NVivo to help analyze data. The results of this study indicate that the management of learning facilities and infrastructure in schools consists of planning, procurement, maintenance, distribution, inventory, deletion, and solutions for management of facilities and infrastructure consisting of planning, namely by preparing human resources and programs, procurement is carried out according to teacher needs, Asset Staff manages maintenance, inventory is carried out by providing records and input in the application, each teacher carries out storage, distribution is carried out to each coordinator, and the deletion process to BKAD and if the goods are indicated as damaged. The implications of this study indicate that the effectiveness of the teaching and learning process is greatly influenced by the quality and availability of optimally managed facilities.